The urinary microbiota: a paradigm shift for bladder disorders?. Issue 5 (October 2016) - Brubaker, Linda; Wolfe, Alan
Abstract : Purpose of review: A resident microbial community [the female urinary microbiota (FUM)] exists within the female bladder of many adult women. Information about the FUM is likely to modify the diagnosis, prevention and treatment of adult women with urinary disorders. This review highlights key findings from recent literature relevant to adult, nonpregnant women. Recent findings: Similar to other human microbial communities, the FUM varies in its characteristics, including organism diversity and predominant organism identity. Recent literature reveals previously undetected organisms and community characteristics that appear associated with certain urinary symptoms, including urinary tract infection and urgency urinary incontinence. The role of individual organisms may range from beneficial to pathogenic and may vary on the basis of an individual's FUM characteristics. The simple dichotomy of 'infected' or 'sterile' no longer sufficiently captures the microbiological complexity of the female bladder. Summary: Deeper understanding of the FUM should yield better methods to restore the microbiota to a healthy state, providing symptom relief. Opportunities to modify the FUM without antibiotic use are exciting possibilities for future research; stand-alone antibiotic use may be reevaluated to improve treatment precision. Long-standing nomenclature for conditions such as asymptomatic bacteriuria and urinary tract infection will likely require modification.